Reconstruction of the Abolition of Compensation Pay-ments Towards Justice for Convicts - Aji Sumbara; Achmad Faishal; Suprapto Suprapto (Law and Justice research journal, 2026)
This study explores the reconstruction of the abolition of compensation payments to foster justice for convicts, specifically evaluating the intersection between Law No. 31 of 1999 and Law No. 20 of 2001. The research addresses the persistent legal dilemma where state loss recovery mechanisms often overlook the fundamental rights and socio-economic realities of prisoners. Under the current regime, the imposition of substitute imprisonment for unpaid financial obligations is perceived as a "layered punishment" that undermines human dignity and fails to reflect proportional justice. The analysis reveals that the retributive orientation established in Law No. 31 of 1999 results in a "lose-lose" outcome: the state remains uncompensated while the financial burden of correctional costs increases due to extended incarceration. By integrating the fiscal and state financial management principles found in Law No. 20 of 2001, this research proposes a shift toward more proportional and restorative asset recovery. The study concludes that the role of the Prosecutor must be reoriented toward accurate asset tracing and the implementation of humane payment schemes. Future legal reforms must ensure that the state's interest in fiscal restoration does not sacrifice the convict's basic rights, prioritizing distributive justice to create a more humane anti-corruption framework.